Optimal mass of the arm segments in throwing: A two-dimensional computer simulation study - Fasbender, P.; Korff, T. J.; Baltzopoulos, V. B.; Linthorne, N. P. (European Journal of Sport Science, 2021)
Producing a high release speed is important in throwing sports such as baseball and the javelin throw. Athletes in throwing sports might be able to achieve a greater throwing speed by improving the effectiveness of the kinetic chain. In this study a two-dimensional computer simulation model of overarm throwing was used to examine the effect of changes in forearm mass and upper arm mass on the release speed of a lightweight (58 g) projectile. The simulations showed that increasing the mass of the forearm decreases release speed, whereas increasing the mass of the upper arm initially increases release speed. For a given forearm mass there is an optimal upper arm mass that produces the greatest release speed. However, the optimal upper arm mass (5-6 kg) is substantially greater than that of an average adult (2.1 kg). These results suggest that athletes might be able to throw faster if they had a stronger tapering of segment mass along the length of their arm. A stronger taper could be readily achieved by attaching weights to the upper arm or by using hypertrophy training to increase the mass of the upper arm. High-speed overarm throwing is a complex three-dimensional movement and this study was a preliminary investigation into the effect of arm segment mass on throwing performance. Further simulation studies using three-dimensional throwing models are needed to generate more accurate insights, and the predictions of the simulation studies should be compared to data from experimental intervention studies of throwing sports.